The Impact of Social Media Use on Social Interaction in Contemporary Society - Azzaakiyyah, Hizbul Khootimah (PT. LITERASI SAINS NUSANTARA, 2023)
The use of social media has become a phenomenon that dominates human life in the contemporary era. This phenomenon raises important questions regarding the impact of social media use on social interactions in contemporary society. This research will explore how social media affects intergroup interactions, including in the context of social groups, communities, and social movements. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study found that the use of social media has brought about profound changes in the patterns of social interaction in contemporary society. This phenomenon has complex impacts, including increased global connectivity, changes in the way individuals construct social identities, and providing a platform for social movements. However, it needs to be recognised that these impacts are not only positive, but also present challenges such as social isolation, unhealthy comparisons, and the spread of harmful information.